Development of Student Worksheets Based on The Search, Solving, Create and Share (SSCS) Learning Model to Improve Critical Thinking Skills in Biology Learning for Third Level (XII) of Senior High School SMA Negeri 1 Pantai Labu - Desvica Simanullang; Ashar Hasairin Harahap; Martina Restuati (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
This project aims to (1) evaluated Student Worksheets (called as LKPD) based on Search, Solving, Create, and Share (SSCS) for material, design, and teacher response learning experts. (2) assess Search, Solving, Create, and Share (SSCS)-based Student Worksheets. This study used descriptive data analysis at SMAN 1 Pantai Labu. This Reserarch & Development follows Bord and Gall's development approach. The model has ten steps: research and information collection, planning, preliminary product development, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, and final product revision. In 2023, Third Level (XII) students at SMA Negeri 1 Pantai Labu tested the Student Worksheets, which was developed at Medan State University. A validation expert team-approved Student Worksheets is the product, based on Search, Solving, Create, and Share. The material expert team rated the Student Worksheets "very good" based on the average percentage of 85.33%, design experts at 90.64%, learning design experts at 88.50%, teacher respondents at 93.06%, individual test of 82.50%, small group test of 90.73%, large group test of 93.36%, and t test value (T count=3.468 and T table=2.042). The Student Worksheets (LKPD) based on SSCS (Search, Solve, Create, and Share) models in Third Level (XII) biology was approved for classroom use